Involvement and participation of small-scale fishers’ organizations in the Azorean Islands - São Marcos, Rita (2021)
International regulatory bodies such as the United Nations (UN) and its Food and Agriculture Organization (FAO) have widely recognized and highlighted the importance of small-scale fisheries as catalysts for sustainable growth and local development. Similarly, the United Nations Department of Economic and Social Affairs (UNDESA) has reported on the need for a change in governance structures, practices and procedures to enable full participation of community organizations as stewards in sustainable development and marine resource management. Despite this growing interest and attention, both by scholars and intergovernmental agencies, small-scale fisheries have long suffered from marginalization and neglect and still face multiple challenges. Declining marine fish, conflicts and competition with other fishing and non-fishing sectors, and, more importantly, bio-economic modeling and policy making strategies that have favoured economic efficiency and environmental sustainability over the social impacts these policies and decision making may have on small-scale fishing communities. This presentation aims to reflect on the role that small-scale fishing communities play in fisheries governance and policy making. Through and inductive approach that follows qualitative methodological and epistemological principles of inquiry, this presentation will look at small-scale fishers’ agency and participation in the Azorean Islands. It will analyse, specifically, the perspectives and understandings of Azorean fishers’ organizations on environmental policy building and maritime resource management: (1) How are fishers’ organizations involved in decision and policy making? (2) What perspectives do they have on how fisheries, the ocean and its different uses have been managed and governed? (3) What strategies do they envision and defend?